ANALISIS PERPINDAHAN MEREK (BRAND SWITCHING) PENGGUNA HANDPHONE NOKIA SERI E DI BANDAR LAMPUNG (STUDI PADA MAHASISWA IBI DARMAJAYA FAKULTAS ILMU KOMPUTER) - Budiasih, Trisna; -, Aswin (Jurnal Manajemen dan Keuangan, 2012)
The existence of a brand in a product is very important as a part of image development of a product on the market. Amid the competition of many products of mobile phone, a brand switching is inevitable. This phenomenon happens to the product of NOKIA particularly E Serial. This research is aimed at measuring the degree or volume of user possibility in brand switching from NOKIA brand product E Serial to Mitto brand of QWERTY model and other products of mobile phone. The researcher uses descriptive method in doing this research. It describes the condition or phenomena. The population and sample of the research are 79 students of IBI Darmajaya from the Faculty of Computer Science. The result of the research turned out that the user pattern of mobile phone brand switching of Nokia E Serial is gained from 33 respondents. 15 (41,1%) respondents remain using Nokia E Serial,13 (38,2 %) respondents switched to Mitto brand mobile phone model QWERTY and 5 (14,7%) respondent switched to other brands. The user pattern of the brand switching of Mitto mobile phone model QWERTY is gained from 31 respondents. 10 (32, 3%) respondents switched to Nokia E Serial, 17 (54,8%) respondents remain using mobile phone of Mitto model QWERTY and only 4 (12, 9%) respondents switched to other mobile phones. The other user pattern of mobile phone brand switching is gained 12 respondents. 7 ( 58,3%) respondents switched to Nokia product E Serial, 5 ( 35,7%)respondents switched to Mitto brand product model Qwerty and only 7 (50,0%) respondents who use other brands of mobile phone rather than Nokia E Serial and Mitto model Qwerty. From the matrix of probability it is predicted that the growth of market-share will be mainly gained by Nokia E Serial which is equivalent with 6.8%.In the future time, Mitto model Qwerty will get increased of its market-share which is equivalent with 0,6 %. However, other mobile phone products (other than Nokia E Serial and Mitto model QWERTY) will get decreased of its market-share which is equivalent with 26, 5 %.Keywords : Brand Switching, Market-Share, Markov Chain